2023
DOI: 10.1111/csp2.12880
|View full text |Cite
|
Sign up to set email alerts
|

Motivating relational organizing behavior for biodiversity conservation

Abstract: As biodiversity loss and climate change accelerate, more people worldwide are engaging in conservation behaviors to “do their part.” Yet, individual behavior change alone is insufficient for the large‐scale, rapid change needed to address these crises. Relational organizing, which involves individuals reaching out to others in their social network, can enhance the speed and scale of conservation behavior change and address the complex, collective action nature of many conservation problems. However, many peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Relational organizing is used in conservation that recognizes how people are more likely to adopt new behaviors and engage in conservation efforts when they feel a sense of community and shared purpose (Burn, 1991;Abrahamse and Steg, 2013). It involves intentionally building connections with people who have a shared interest and using these connections to encourage others to engage in conservation behaviors (Jones and Niemiec, 2023). In the Bow Valley, the WildSmart Trusted Messengers project is an example of relational organizing.…”
Section: Messaging Needs To Be Clear and Consistentmentioning
confidence: 99%
“…Relational organizing is used in conservation that recognizes how people are more likely to adopt new behaviors and engage in conservation efforts when they feel a sense of community and shared purpose (Burn, 1991;Abrahamse and Steg, 2013). It involves intentionally building connections with people who have a shared interest and using these connections to encourage others to engage in conservation behaviors (Jones and Niemiec, 2023). In the Bow Valley, the WildSmart Trusted Messengers project is an example of relational organizing.…”
Section: Messaging Needs To Be Clear and Consistentmentioning
confidence: 99%
“…Injunctive norms are a person's perceptions of how they should behave and descriptive norms are perceptions of how other people are behaving (Cialdini et al, 1990). Recent studies have found that social norms may be particularly important for motivating more collective actions (see Howell et al, 2015; Jones & Niemiec, 2023; Niemiec et al, 2019). However, other studies have not found normative interventions to be highly effective in motivating conservation behavior (see Berl et al, 2022; Byerly et al, 2019; Niemiec, Sekar, et al, 2020 as examples).…”
Section: Introductionmentioning
confidence: 99%